Sikap Ibn Kathīr Terhadap Riwayat Isrāiliyāt Dalam Tafsir Al-Qur’ān Al-‘Aẓīm - raudhatul raudhah; Misnawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study examines Tafsir Al-Qur’ān al-‘Aẓīm by Ibn Kathīr with a focus on its interpretive methodology and Ibn Kathīr’s attitude toward Isrāiliyyāt narrations. This research employs a qualitative approach using library research methods. The findings reveal that Ibn Kathīr applied the tahlili method with a bil ma’thur approach, interpreting the Qur’an through the Qur’an itself, prophetic traditions, and narrations from the companions and tabi‘in. In dealing with Isrāiliyyāt, Ibn Kathīr did not accept such narrations uncritically, but rather examined and evaluated them carefully. He classified Isrāiliyyāt into three categories: narrations that are acceptable because they conform to Islamic teachings, narrations that must be rejected because they contradict the Qur’an and authentic Sunnah, and narrations toward which he adopted a position of tawaqquf, neither affirming nor denying them due to the absence of clear evidence. Therefore, Ibn Kathīr’s tafsir is characterized as a narration-based exegesis with a critical approach and remains an important reference in Qur’anic studies today.